Pendampingan Kelompok UMKM di Garut Dalam Penggunaan Dompet Digital Untuk Mendukung Ekonomi Digital - Rina Kurniawati; Leni Fitriani; Muhammad Rikza Nashrulloh (Journal of Community Development, 2025)
The community service program aimed to enhance the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Garut Regency through the implementation of digital wallet technology. Addressing the challenges of market access and financial management faced by MSMEs, the program developed an application called MitraREID. This application was designed to assist MSMEs in managing transactions, recording expenses, generating financial reports, and optimizing product management. The implementation process included socialization, intensive training, application deployment, and technical assistance involving the UMKM community, Mikromega, in Garut. The results indicated a significant improvement in the MSMEs' ability to utilize digital technology for daily operations. The MitraREID application facilitated business management, enhanced transaction efficiency, and allowed MSMEs to structure their financial management more effectively. The program's impact was quantitatively measured by pre- and post-test scores, which showed an increase from an average of 79/100 before training to 99/100 after training. This significant improvement demonstrated the enhanced digital skills and understanding of participants in utilizing digital wallet technology to support their business operations, enabling them to compete more effectively in local and national markets.